Chronic pericarditis in a naturally Leishmania (Leishmania) chagasi infected dog - Silva , Bruno C.; Rachid , Milene A.; Vieira , Fernanda G.; Figueiredo , Maria M.; Valle , Guilherme R.; Tafuri , Wagner L.; Toledo Júnior , João C.; Ribeiro, Vitor M. (Brazilian Journal of Veterinary Pathology, 2009)
Visceral Leishmaniasis is an infection disease of chronic evolution caused by the protozoan Leishmania sp. The main clinical manifestations in dogs are anemia, progressive weight loss, lymphadenopathy, hepatomegaly, and cutaneous lesions. The heart involvement in visceral leishmaniasis has been rarely reported. The aim of this work was to describe the presence of amastigote forms of Leishmania sp. and associated lesions in the heart of naturally infected dog. For diagnosis analysis, serological tests for anti-Leishmania antibodies and fine-needle aspirative bone marrow cytology were used. The samples (right ventricle and ear skin) were histologically evaluated and processed for imunodetection of Leishmania sp. The most significant histological change was an intense, non-specific, chronic pericarditis associated with intracytoplasmatic amastigotes within macrophages. The tissue parasitism was confirmed through positive imunomarcation. This is a first report of pericardium compromisement of naturally Leishmania infected adult dog.